Resolution of Acanthamoeba Keratitis with Adjunctive Use of Oral Miltefosine. (17th February 2021) - Avdagic, Ema; Chew, Hall F.; Veldman, Peter; Tu, Elmer Y.; Jafri, Mansab; Doshi, Rutvi; Boggild, Andrea K.; Reidy, James J.; Farooq, Asim V.
ABSTRACT: Purpose : To report a series of cases demonstrating the resolution of Acanthamoeb a keratitis (AK) with adjunctive use of oral miltefosine. Methods : Retrospective case series. Results : The first case was a 27-year-old female who presented with severe pain and photophobia. The diagnosis of AK was made with confocal microscopy, which revealed a significant burden of stromal cysts. After approximately 2 weeks of adjunctive oral miltefosine therapy, there was a severe inflammatory response within the cornea followed by quick resolution of the AK. The second case was a 31-year-old male in whom the diagnosis of AK was confirmed by culture and polymerase chain reaction. Adjunctive oral miltefosine was started 3 months after presentation, leading to a quick resolution. Conclusions : Oral miltefosine may have cysticidal properties and should be considered as adjunctive therapy for the treatment of AK, particularly in cases with a significant burden of cysts or in cases recalcitrant to other treatments.